REFORESTATION AS AN ENVIRONMENTAL PRESERVATION OPTION IN THE QURAN - Noor, Muhammad Fauzi; Maulid, Izza Abdi Nur (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
This study discusses the importance of reforestation as one of the environmental conservation options from the perspective of the Qur'an. The global environmental crisis, including deforestation, climate change, and ecosystem degradation, has had a significant negative impact on human life and the sustainability of nature. With a descriptive qualitative approach based on literature, this study explores the theological values ​​contained in the Qur'an, such as human responsibility as caliphs on earth, the importance of maintaining the balance of nature, and the prohibition of damaging the environment. The results of the study indicate that reforestation is not only an ecological action, but also part of worship that reflects human obedience to Allah SWT. Reforestation provides ecological benefits in the form of improving the carbon cycle, preventing erosion, and increasing biodiversity, while supporting the social and economic sustainability of the community. By integrating Islamic spiritual values, reforestation becomes a real step in maintaining the sustainability of nature, improving human relations with the environment, and fulfilling the divine mandate to maintain the earth as a blessing for all living things. This study emphasizes that reforestation is a strategic solution that combines ecological and theological approaches, so that it can be a foundation for building sustainable environmental awareness rooted in religious values.